LITERASI BENCANA DALAM PEMBELAJARAN GEOGRAFI PADA KURIKULUM MERDEKA BELAJAR - Agus Hale Manek (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2023)
The ability to handle disasters is important to do. The ability to handle from emergency response to recovery requires knowledge related to the disaster itself. Nowadays, it is realized that the process of building disaster-related knowledge is carried out through education. Through education on cognitive aspects and skills in evaluating disaster risk, increasing preparedness and reducing vulnerability to disasters is developed. Literacy demands and teaching materials about disasters are a priority in providing understanding and fostering understanding about disasters. Geography learning studies natural phenomena that influence humans. So that in learning geography students are faced with real problems and solutions. The development of the current independent curriculum can be an alternative to address these challenges. This is because the independent curriculum presents a variety of intra-curricular learning so that it will be more optimal to provide understanding and strengthen competence. In addition, in the independent curriculum there is flexibility to choose learning tools according to interests and needs. The method used in this writing is a literature review of various literature collected then analyzed and conclusions drawn. The aim is to reveal that learning geography in the independent learning curriculum can facilitate and foster an understanding of disaster literacy.